(untitled) (Northern International Medical College Journal, 2015)
Cerebral malaria (CM) is the most severe neurological presentation of acute falciparum malaria. It is a medical emergency, the hallmark of which is the presence of coma probably due to diffuse encephalopathy. A compromised microcirculation with sequestration of parasitized erythrocytes is central to the pathogenesis of cerebral malaria. The death is unacceptably high even with effective antimalarials in tertiary care hospital. The mainstay of treatment of cerebral malaria include prompt diagnosis and early institution of effective antimalarial therapy, recognition of complications, and appropriate supportive management in an ICU. Neurological sequlae are increasingly recognized, but further research on the pathogenesis of coma and neurological damage is required to develop other ancillary treatments Northern International Medical College Journal Vol.6(2) 2015: 45-47